2021
DOI: 10.1016/j.dib.2020.106660
|View full text |Cite
|
Sign up to set email alerts
|

Data on the proximate composition, bioactive compounds, physicochemical and functional properties of a collection of faba beans (Vicia faba L.) and lentils (Lens culinaris Medik.)

Abstract: This dataset is referred to a collection of 41 faba bean ( Vicia faba L.) and 15 lentil ( Lens culinaris Medik.) accessions from the ex situ repository of the Institute of Biosciences and Bioresources of the Italian National Research Council (CNR-IBBR). All the accessions were grown at the experimental farm “P. Martucci” of the University of Bari “Aldo Moro” (41°01′22.1′′ N 16°54′21.0′′ E) during the growing season 2017–2018, according to a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The pea-based texturized protein showed the lowest content of glutamic healthy effect of fatty acids, and lower values are preferable to prevent some coronary diseases (Pleadin et al, 2017). Overall, the fatty acid composition, and the relative indices of atherogenicity and thrombogenicity, was similar to those of other legume species (De Angelis et al, 2021b), suggesting a healthy lipid profile. However, it should be considered that the soy protein is defatted, whereas the oat protein is rich in fat (about 16% as reported in De Angelis et al, 2020).…”
Section: Fatty Acid Compositionsupporting
confidence: 55%
See 1 more Smart Citation
“…The pea-based texturized protein showed the lowest content of glutamic healthy effect of fatty acids, and lower values are preferable to prevent some coronary diseases (Pleadin et al, 2017). Overall, the fatty acid composition, and the relative indices of atherogenicity and thrombogenicity, was similar to those of other legume species (De Angelis et al, 2021b), suggesting a healthy lipid profile. However, it should be considered that the soy protein is defatted, whereas the oat protein is rich in fat (about 16% as reported in De Angelis et al, 2020).…”
Section: Fatty Acid Compositionsupporting
confidence: 55%
“…The methylation was carried out according to the American Oil Chemists Society method Ch 1-91 (AOCS, 1993). The gas-chromatographic apparatus and the conditions of analysis were reported in De Angelis et al (2021b) and were composed of a 7890B gas-chromatograph (Agilent Technologies, Salta Clara, USA) equipped with a flame ionization detector and a fused silica capillary column SP2340 60 m × 0.25 mm × 0.2 μm (Supelco Park, Bellefonte, USA). The identification of each fatty acid was possible by comparing the retention time with that of the methyl ester standards (Merck KGaA, Darmstadt, Germany).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…In silico approaches use computer-aided databases to predict the bioactive peptides in a precursor protein. One commonly used database is BIOPEP, which allows the forecasting of peptides from known amino acid sequences [ 73 ]. Karkouch et al [ 74 ] isolated and identified several peptide sequences from FBH using strong cation exchange chromatography, followed by LC-MS/MS with an orbitrap hybrid mass spectrometer.…”
Section: Bioactivitymentioning
confidence: 99%
“…In the study by Valente et al [ 139 , 140 ], the phenolic composition and antioxidant activity of European FB cultivars varied significantly between cultivars. A study by Baginsky et al [ 73 ] also reported that differences existed in the phenolic profiles among ten immature Chilean faba bean varieties. A comparison of the TPC and flavonoids of 13 faba bean varieties analyzed at various stages of maturity revealed variations in total phenolic content and flavonoid content, with higher levels observed at the maturity stage [ 141 ].…”
Section: Impact Of Processing Technologies On Faba Bean Seeds’ Pharma...mentioning
confidence: 99%
“…Moreover, lentils represent an important source of complex carbohydrates, fibres, minerals, vitamins, polyphenols, and other phytochemicals with several potential health benefits, including anticarcinogenic potentialities, blood pressure-lowering and hypocholesterolemic, and glycemic load-lowering activity [6]. However, these features can vary considerably among different varieties [7][8][9][10]. Therefore, given the large number of cultivars and landraces, general observations about lentil characteristics might sound somewhat limited.…”
Section: Introductionmentioning
confidence: 99%